The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1038/sj.cr.7310146
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between antigen presenting cells and autoreactive T cells derived from BXSB mice with murine lupus

Abstract: npg Systemic lupus erythematosus (SLE) is a typical autoimmune disease involving multiple systems and organs. Ample evidence suggests that autoreactive T cells play a pivotal role in the development of this autoimmune disorder. This study was undertaken to investigate the mechanisms of interaction between antigen presenting cells (APCs) and an autoreactive T cell (ATL1) clone obtained from lupus-prone BXSB mice. ATL1 cells, either before or after γ-ray irradiation, were able to activate naive B cells, as deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Upon activation by self-antigens, cDC can promote lupus development by interacting with T cells and B cells. While in vivo studies of how cDC affect autoreactive T cells are still lacking, in vitro evidence suggests that moDC derived from the bone marrow of lupus mice or from PBMC of SLE patients, upon activation, can promote T cell activation and hamper Treg response [ 39 , 52 , 78 80 ]. It is demonstrated in both mouse and human cell studies that moDC activated by apoptotic cells or cytosolic dsDNA could induce the activation of T cells, including that of autoreactive T cells [ 52 , 79 ].…”
Section: Breakdown Of Immune Tolerance To Self In Sle By Cdcmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon activation by self-antigens, cDC can promote lupus development by interacting with T cells and B cells. While in vivo studies of how cDC affect autoreactive T cells are still lacking, in vitro evidence suggests that moDC derived from the bone marrow of lupus mice or from PBMC of SLE patients, upon activation, can promote T cell activation and hamper Treg response [ 39 , 52 , 78 80 ]. It is demonstrated in both mouse and human cell studies that moDC activated by apoptotic cells or cytosolic dsDNA could induce the activation of T cells, including that of autoreactive T cells [ 52 , 79 ].…”
Section: Breakdown Of Immune Tolerance To Self In Sle By Cdcmentioning
confidence: 99%
“…It is demonstrated in both mouse and human cell studies that moDC activated by apoptotic cells or cytosolic dsDNA could induce the activation of T cells, including that of autoreactive T cells [ 52 , 79 ]. In addition, compared to bone marrow-derived macrophages, bone marrow-derived cDC (BMDC) from lupus-prone mice possessed higher ability to activate autoreactive T cells, suggesting that cDC rather than macrophages are the APC for autoreactive T cell activation [ 78 ]. Moreover, in vitro generated tolerogenic BMDC from SLE patients were less capable of generating Treg cells in vitro than HC BMDC [ 80 ].…”
Section: Breakdown Of Immune Tolerance To Self In Sle By Cdcmentioning
confidence: 99%
“…A previous study has suggested that FasL + B cells and FasL + CD4 CD8 double negative (DN) T cells may contribute to the cytotoxic destruction of Fas + tissues in MRL/lpr mice [3] . In addition, most studies have reported that the hyper-interaction between T lymphocytes and B lymphocytes is involved [4] . Moreover, B cell hyperactivity and spontaneous antibody production have been reported in SLE.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Aging BXSB males developed progressive monocytosis, more pronounced in the peripheral blood than in spleen. 20,21 Although monocytosis itself is inadequate to drive the disease process, 22 progression of renal pathology can be accelerated by systemic exposure of mice to lipopolysaccharide (LPS). 23 The exact role of monocytosis in BXSB remains poorly understood, and it is not clear whether it involves impairment of the functional properties of monocytes.…”
Section: Discussionmentioning
confidence: 99%